High-Throughput Automated Micro-Permethylation for Glycan Structure Analysis - Shajahan, Asif (Anal Chem, 2018)
Permethylation is an essential technique for the detailed structural characterization of glycans by mass spectrometry. However, it requires specialized skills and equipment and is labor-intensive. While this limits glycan analysis to a handful of experts, the increasing awareness of the tremendous importance of glycans in physiological processes of health and disease has drastically raised the demand for detailed structural characterization of glycans. We have developed a simple microplate permethylation method that relies upon solid phase extraction using C18 tips to purify the permethylated glycans. The procedure is easy to perform, making it accessible to non-experts, and fast, promising to accelerate glycan research. A 96-well plate of released glycan samples can be permethylated in less than an hour. The procedure can be carried out without discontinuous steps in an automatic pipette and integrated seamlessly with glycan release and mass spectrometry.